Allogeneic stem cell transplantation for chronic lymphocytic leukemia: Lessons to be learned from minimal residual disease studies - Böttcher, Sebastian; Ritgen, Matthias; Dreger, Peter (Blood reviews, 2011)
Allogeneic stem cell transplantation (alloSCT) is a potentially curative treatment strategy for poor-risk chronic lymphocytic leukemia (CLL). The crucial anti-leukemic principle of alloSCT in CLL appears to be the graft-versus-leukemia effect (GVL). Evidence for GVL in CLL is particularly provided by studies analysing the kinetics of minimal residual disease (MRD). The purpose of this review is to summarize the methodologies of MRD assessment, its proven benefits and its further perspectives for optimizing the outcome of transplantation. Proven value of quantitative MRD monitoring by RQ-PCR or MRD-flow consists in using it as an indicator of long-term disease control and potential cure. As MRD kinetics correlates with GVL activity, its suitability for guiding GVL-inducing immunomodulation is currently under investigation. In conclusion, quantitative MRD monitoring seems to be mandatory to assure safe and effective immunotherapy in the context of alloSCT for CLL, which should, however, be best performed within clinical studies.
Gesehen am 03.06.2022